Implementing Effective Learning Designs : Final Report. - Dalziel, James; Cameron, Leanne (Australian Learning and Teaching Council (ALTC), 2011)
Final report from a project that demonstrated that generic learning designs can serve as pedagogical frameworks to support academic staff in creating new learning experiences. The templates developed can be used by academic staff to tailor exemplary examples to meet the individual lecturer's, and/or course co-ordinator's, particular requirements, whilst providing them with the underlying pedagogical principals involved in the learning design. Academics can readily adapt these learning designs, specify particular activities and/or create resources and supports to suit their own students' needs. A framework and design guidelines were also created so that new learning designs can be effectively described to produce a comprehensive scaffold to assist designers in the development of new learning designs and supportive activities. This project also explored the issues to emerge from the implementation of learning designs, and identified barriers to their widespread adoption and ways of overcoming them. These findings underpin the implementation of learning design templates which address these adoption challenges in their design and streamlines the planning process. Learning design for the higher education environment is a complex task, especially in light of the increasing diversity of the student body. Learning materials need to be designed to take advantage of different student ability levels, learning approaches and media, and curriculum developed to support a huge variety of outcomes that are often discipline specific. This project provided some basic scaffolding to help academics produce good quality designs without having to be experts in pedagogy.